2021
DOI: 10.7554/elife.62122
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the endemicity and seasonality of clinical malaria for intervention targeting in Haiti using routine case data

Abstract: Towards the goal of malaria elimination on Hispaniola, the National Malaria Control Program of Haiti and its international partner organisations are conducting a campaign of interventions targeted to high-risk communities prioritised through evidence-based planning. Here we present a key piece of this planning: an up-to-date, fine-scale endemicity map and seasonality profile for Haiti informed by monthly case counts from 771 health facilities reporting from across the country throughout the 6-year period from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The regions of Haiti included as school sampling sites have high heterogeneity in malaria disease burden and vector density ( Frederick et al., 2016 ; Cameron et al., 2021 ). High levels of vector exposure can still occur even when P. falciparum is not prevalent in the human population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regions of Haiti included as school sampling sites have high heterogeneity in malaria disease burden and vector density ( Frederick et al., 2016 ; Cameron et al., 2021 ). High levels of vector exposure can still occur even when P. falciparum is not prevalent in the human population.…”
Section: Discussionmentioning
confidence: 99%
“…Hispaniola, an island composed of the Dominican Republic and Haiti, is the only area in the Caribbean with endemic malaria, with Plasmodium falciparum as the primary species. Though recent malaria transmission in Haiti has been relatively low ( Lucchi et al., 2014 ; Jules et al., 2022 ), heterogeneity by spatial, individual, and environmental factors accentuates the need for enhanced surveillance methods to characterize higher-risk regions and population subgroups to further move towards malaria elimination ( Boncy et al., 2015 ; Cameron et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other situations, disease-specific risk could also be accounted for. For instance, in order to prioritise areas where significant malaria transmission is identified, the placement algorithm can be modified to include malaria incidence into the model in addition to capacity and walking time constraints, either by giving more weight or lower population numbers per CHW in malaria endemic areas, or by restricting the allocation to the areas where malaria risk is considered present with a predefined probability (exceedance probability maps) [34]. Additionally, detailed workload data can be used to calibrate the maximum capacity per CHW, which is very specific to the characteristics of a given CHW program [32].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The analysis focused exclusively on physical accessibility and did not consider other determinants of access to care, such as financial accessibility [4], the quality of services provided [36], and more generally demographic, economic and social factors impeding or facilitating healthcare access [37,38]. This analysis also focused exclusively on population coverage assuming that CHWs serve all individuals equally and therefore did not consider how the decisions regarding the geographical distribution of CHWs could depend on the presence of epidemiological risks, for example higher malaria risk in the Grande-Anse and Sud departments [34], or particular needs in specific population subgroups. Furthermore, the choice of thresholds for the maximum distance and maximum population in urban and rural areas could lead to border effects and gives a tendency for the model to place more CHWs in high-capacity areas, in order to minimise their total number.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…This differs from standard Bayesian inference where PK and PD models are inferred simultaneously. More examples that adopt modularized Bayesian inference for this purpose include: Li et al (2013), which removes the influence from the suspect highest streamflow observations in hydrological modeling; Mikkelä et al (2019), which removes the influence from the less "valid" reported human salmonellosis cases data to the estimation of the distribution of salmonella subtypes in the food sources; Arambepola et al (2020), which removes the influence from the less reliable malaria incidence data to the malaria prevalence estimation; and Cameron et al (2021), which applies modularized Bayesian inference to focus on the estimation of endemic transmission intensity of malaria.…”
Section: Introductionmentioning
confidence: 99%